The study of speech acts in the conversation of KGRE's celebities program - Moch. Maskuri (Pro-ELLitera, 2024)
This study is about the speech acts used at celebrities’  conversation program in KGRE. The writer tries to analyze the forms and the meaning of utterances used by the participants in celebrities conversations program of KGRE.’ The writer uses Austin’s theory to analyze the kinds of speech acts. He uses Yule’s and Searle’s theory to analyze the forms of the utterances and the meaning of utterances. The writer uses Prsst program 4027 to analyze the intonation uses by the participants in the conversation. The result of this study shows that the participants use three kinds of speech acts. They are locution, illocution and perlocution. He participants use Yule’s three kinds of utterances. They are declarative, interrogative, and imperative. Declarative and interrogative are found in every fragment. While, imperative is only found in fragment 14.  All participants use two kinds of utterance meanings. They are directive and representative. This kind of utterance meaning is found in every fragment. After analyzing the utterances of the conversation, the writer finds that the participant use falling, flat and rising intonation.